Hypoglicemia related to big Haemangiopericitoma: a difficult diagnostic definition - Siniscalchi, Carmine; Basaglia, Manuela; Cunzi, Davide; Merla, Simona; Mattioli, Maria; Gaibazzi, Nicola; Volpi, Riccardo (Acta Biomedica Atenei Parmensis, 2015)
We describe the case of a 91 years old woman admitted to our department for dyspnea associated with drowsiness. At the admission to the Emergency Room the patient stay in a comatose state and blood tests performed showing severe hypoglycemia (38 mg/dl at admission in non diabetic patient). Anamnestic history: multifactorial anemia; frequent hospitalizations for heart failure; AMI treated with stenting; in 1986 Haemangiopericytoma resection in the right iliac region; in 2006 palliative surgery for recurrence with residual mass. Blood tests showed lower levels of insulin and normal C- peptide serum concentration in correspondence of low glucose concentration (in relation to continuous and adequate parenteral nutrition), IGF 1 and GH level was respectively suppressed (IGF1=47 ng/ml whit normal range 97-331 ng/ml) and normal/low (GH 0.43 uUI/mL whit normal range 0.06-14.00 uUI/mL).Therefore hypoglycemia appeared related to paraneoplastic production of IGF -2.